A relação transitiva entre sociedade, tecnologia e matemática: aportes relativos à formação profissional em um curso superior de informática - Bortolete, Juliano Cavalcante (2011)
This work seeks to discuss and comprehend, through qualitative research approach, the influence that Mathematics has over technological and social development. The theoretical contributions employed in this study point to the fact that currently people live in an informational society, whose operation is based on the pillars of information technologies which, in turn, are driven by Mathematics. From these assumptions, mediated by the perspective of Critical Mathematics Education, we sought to find an application capable of explaining the interfaces between Mathematics and technology, as well as their implications for the contemporary world, which led to the use of the Vector Model for Information Retrieval, theme present in Discrete Mathematics syllabus, as the basis for the building of search engines by the students of Analysis of System Development in a public college in São Paulo. Data collection was carried out by means of questionnaires and observations in the classroom, trying to identify from the students answers their concerns about the professional use of the contents of disciplines related to Mathematics. Because of dissociation, from the student s point of view, regarding the applicability of Mathematics to technological and professional development, they were invited to build search engines based on mathematical concepts present in the Vector Model mentioned above. The analyses showed that the construction process of applications led to a change of perception and attitude towards the mathematical knowledge, its insertion in the context of technological production and its use in real professional situations